Factors that Influence Consumer to Choose Islamic House Financing in Hong Leong Bank Berhad - Noriza, Abd Aziz (2009)
Islamic House financing has been introduced and implemented in Hong Leong Bank Berhad since 1999. However, we do not know how far justification level of consumer acceptance and perception of this Islamic product. This study deals with several factors namely level of perceived awareness, understanding and perception towards consumer purchase decision on Islamic house financing product in Hong Leong Bank Berhad. To see how far that Islamic house financing product can be fully accepted by consumer in Hong Leong Bank, quantitative method has been used in this research. 200 questionnaires have been distributed to the respondent in Hong Leong Bank however the researcher only received 100 questionnaire answers from the respondent fully intact. Researcher found that these three factors namely level of perceived awareness, understanding and perception has strong relationship that influenced consumer towards customer purchaser decision on Islamic house financing in Hong Leong Bank. In order to achieve this research objective, researcher used F-Test (whole analysis), T-Test (partial analysis) and Pearson Correlation. Through F-Test, it can be identified that factors of level perceived awareness, understanding and perception has a positive significant that influenced consumer to choose Islamic house financing product in Hong Leong Bank Berhad. Through T-Test, factors of independent variables that influenced customer purchase decision can be identified and measured. Pearson Correlation is used to identify positive significant relationship between independent variables and dependent variable. From this research, Hong Leong Bank can identify what are the factors that influenced customer to choose Islamic house financing. Based on data analysis received from the respondents who used Islamic house financing, it can be identified that overall factors of level perceived awareness, understanding and perception gives positive significant influence to consumer's decision to choose Islamic house financing in Hong Leong Bank.